Analisis Faktor-Faktor Yang Berhubungan Dengan Keuntungan dan Tingkat Kelayakan Usaha Pedagang Buah di Pasar Kepuh Kecamatan Kuningan Kabupaten Kuningan Jawa Barat - Deni Mustopa; Kuswarini Sulandjari; I Putu Eka Wijaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Income from trading business contributes to the family income of fruit traders. Fruit traders in Pasar Kepuh bear the business risk, reducing the economic value of the fruits. This study aims to analyze costs, revenues and profits as well as analyze the factors that influence the business profits of fruit traders. Determination of samples with saturated sampling method, as many as 21 traders. Primary data were obtained through interviews and observations. Data were analyzed using income, business service, correlation. The results showed: The average cost of each trader is Rp. 8,266,575 per week, the average income of each trader is Rp. 10,463,524 per week, the average profit of traders is Rp. 2,196,949 per week; The fruit merchant business was declared feasible with the R/C ratio showing 1.27. The variables of capital and length of business have a significant relationship to profits, while the variables of age, education and number of dependents do not have a significant relationship to profits.